The Role of Healthcare Leaders in Promoting Vaccine Acceptance in Saudi Arabia - Al Zahrani EM (Dove Medical Press, 2024)
Eidan M Al Zahrani Physical Therapy Department, Prince Sultan Military College of Health Sciences, Dhahran, Saudi ArabiaCorrespondence: Eidan M Al Zahrani, Physical Therapy Department, Prince Sultan Military College of Health Sciences, Dhahran, Saudi Arabia, Tel +966 13 840 5431, Email edan@psmchs.edu.saBackground: Several vaccines have been recommended by the health authorities in recent years and have been opposed by debates, lack of public trust, and variable levels of hesitance that resulted in increased anti-vaccination advocacy and a subsequent reduction in vaccination rates worldwide.Purpose: This study aimed to explore the community's perceptions of the role of healthcare leadership in promoting vaccine acceptance.Methods: This cross-sectional study used a validated questionnaire designed according to the study's objectives for a heterogeneous purposive sample of individuals over 18 years old in Saudi Arabia. Participants completed the questionnaire online via a link provided by multiple social media platforms.Results: The study included 7159 participants with various demographical features. On a five-point Likert scale, the average level of agreement on the role of healthcare executives in promoting vaccines was 3.76. The average level of agreement about the role of healthcare leaders in promoting vaccines was 3.76 out of five. Men were more likely than women to agree on healthcare worker's influence, 63.6% and 58.6%, respectively (P < 0.001). The ages of participants showed a favorable correlation with their level of agreement on the role of healthcare leaders in promoting vaccines (P < 0.001). The level of agreement on healthcare leader's role in promoting vaccines was inversely proportional to the education level (P < 0.001). The retired group reported the highest score, followed by the employed ones (P < 0.001).Conclusion: Unlike other political and religious leaders, this study indicates that healthcare professionals significantly impact vaccine hesitancy and uptake. Despite rising vaccine hesitancy, healthcare leaders remain more trustworthy providers of guidance and influence over vaccination decisions than others. In addition, the health leader's factual message boosts people's self-esteem and helps them decide to be vaccinated.Keywords: vaccine hesitancy, healthcare leadership, Saudi Arabia